AROMATERAPI LEMON DAN SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE TERHADAP PERUBAHAN TEKANAN DARAH LANSIA DENGAN HIPERTENSI - Sari, Adinda Kurnia; Lilyana, Maria Theresia Arie; Prabasari, Ninda Ayu (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2026)
Introduction: Older adults are at high risk of developing hypertension due to degenerative processes in the heart and blood vessels, which can lead to complications such as stroke, heart failure, myocardial infarction, and even death. Blood pressure can be managed through nonpharmacological or complementary therapies, such as Lemon Aromatherapy and Spiritual Emotional Freedom Technique (SEFT)Objective: To determine whether the administration of SEFT and lemon aromatherapy has an effect on blood pressure in the elderly. Methods: A pre-experimental one-group pretest-posttest design was used, with the intervention consisting of Spiritual Emotional Freedom Technique (SEFT) and lemon aromatherapy administered over 3 days. Participants (n) = 30 elderly individuals diagnosed with stage 1 hypertension. Results: The mean systolic blood pressure decreased from 150.3 ± 5.266 mmHg to 141.1 ± 5.234 mmHg, while diastolic blood pressure decreased from 93.266 ± 2.476 mmHg to 87.3 ± 2.380 mmHg after the intervention. Conclusion: The combination of lemon aromatherapy and Lemon Aromatheraphy has been shown to help lower blood pressure and can therefore be used as a complementary therapy for elderly individuals with hypertension.